Perancangan dan Pembuatan Sistem Informasi Administrasi Pada TK Anak Ceria - Soetedjo, Ginno Samuel Tangkas; Rostianingsih, Silvia; Dewi, Lily Puspa (Jurnal Infra, 2014)
For years, TK Anak Ceria does not have a centralized and organized academic information system. The data is being kept in archives and this situation complicates the school to control the schoolâs work and quality, such as studentâs grades data that are still kept in paper archives, unstructured studentâs data, manually written cash flow transaction and others.Based on that problems, the solution is to make a design and implementation of web based school administration information system on TK Anak Ceria. The system will facilitate the arrangement and data storage for the school administration data, and the schoolâs finance. This administration information constructed using SQL Server 2005 and Visual Studio 2005.From the implementation and application setting, it can be concluded that the system is useful enough to be used as school administration information system. However, it also can be concluded that there is a lack of interface design in the report forms.